Efficient Montgomery Modular Multiplication by using Residue Number System - Khani, Elham (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Residue number system is a carry free system that performs arithmetic operation on residues instead of the weighted binary number. By applying Residue Number System (RNS) to Montgomery modular multiplication the delay of modular multiplication will be decreased. Modular multiplication over large number is frequently used in some application such as Elliptic Curve Cryptography, digital signal processing, and etc.By choosing appropriate RNS moduli sets the time consuming operation of multiplication can be replaced by smaller operations. In addition because of the property of RNS, arithmetic operations are done over smaller numbers called residues. In this paper by choosing appropriate moduli sets the efficiency of conversion from RNS to RNS that is the most time consuming part of the Montgomery modular multiplication will be increased.